2017
DOI: 10.18203/2394-6040.ijcmph20171786
|View full text |Cite
|
Sign up to set email alerts
|

A study to assess the knowledge of mothers on home based neonatal care at selected area of rural Bangalore

Abstract: Background: The new born signifies the beginning of life and provides a foundation for future health of the nation.  New born care is strongly influenced by women’s social status, health status, home care practices for mother and new born care services. Therefore, the present study has been designed to assess the Knowledge of mothers on home based neonatal care especially among rural mothers.Methods: After the institutional ethical clearance, five hundred mothers having infants belong to Rural Bangalore were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, in some people, education does not affect it because it is more influenced by the environment that the individual accepts. 20 The majority of respondents in this study were found to have postpartum blues. It is because postpartum blues are often neglected and not handled properly.…”
Section: Discussionmentioning
confidence: 70%
“…However, in some people, education does not affect it because it is more influenced by the environment that the individual accepts. 20 The majority of respondents in this study were found to have postpartum blues. It is because postpartum blues are often neglected and not handled properly.…”
Section: Discussionmentioning
confidence: 70%